The Informational Culture of the Future Primary School Teacher as the Priority of the Quality Improvement of the Linguistic Disciplines - Hreb, Maria Mykhailivna; Hrona, Nataliya Victorivna (Journal of History Culture and Art Research, 2019)
Within the article, the peculiarities of the improvement of the informational culture of the future teacher of the primary school as the process of knowledge and means which influence the actualization of the informational activity were determined. During this activity, the future teacher expresses his or her aesthetic tastes, requirements, interests, ideas, judgments, beliefs and intellectual abilities which begin to form within the student due to the leadership of the teacher. The goal of the article is the elucidation of modern methodical approaches to the improvement of the informational culture of the future teacher during the process of studying linguistic disciplines. The subject of the research is the pedagogical conditions of the increasing of the informational culture of the future specialist. The theoretical-methodological basis of the research is made up with: classical and modern attainments of the world and national pedagogics, modern research on problems of the education’s informatization, the activity theory of teaching and development of the personality. For the achievement of the determined goal and the solution of the determined tasks there was implemented the complex of research's methods: theoretical – analysis of the psychological, pedagogical, educational-methodical literature on the research's problem; synthesis and generalization, comparison; work with the experience of teachers of high educational institutions, determination of the conceptual apparatus of the research; empirical – observation and analysis of the pedagogical phenomena and processes, collective and individual conversations with the aim of the revealing of the main contradictions and disadvantages within the education, within methods and educational processes for the detection of the students' understanding of the informational means of teaching, oriented on the increasing of their informational culture. Within the article, there were also determined the criteria of the informational culture of the future primary school teacher: informational activity, informational consciousness, informational-communicative readiness, informational thinking, and informational readiness. It is proved that the increasing of the informational culture of the future specialist for the primary school is able to become such an instrument which would give the opportunity to improve simultaneously the quality of the education and to become the environment and to provide the environment within which the new culture of teaching would be able to develop in. The strategic goal of the development of a system of increasing the qualification of the pedagogical staff foresees the augmentation of the openness and accessibility of the educational services and orientation on the individual demands of each student.